2021
DOI: 10.3390/catal11081014
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Combined Adsorption−Ozonation Process for Phenolic Wastewater Treatment in a Continuous Fixed-Bed Reactor

Abstract: This work studied the removal of phenol from industrial effluents through catalytic ozonation in the presence of granular activated carbon in a continuous fixed-bed reactor. Phenol was chosen as model pollutant because of its environmental impact and high toxicity. Based on the evolution of total organic carbon (TOC) and phenol concentration, a kinetic model was proposed to study the effect of the operational variables on the combined adsorption–oxidation (Ad/Ox) process. The proposed three-phase model express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Researchers demonstrated that the metal doped nanostructures and nano-compounds are increased and improved their catalytic activity and ability for adsorption of toxic gas molecules [23]. The metal doped on surfaces of nanostructures are catalytic positions and possible sites for adsorption of toxic gas molecules [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers demonstrated that the metal doped nanostructures and nano-compounds are increased and improved their catalytic activity and ability for adsorption of toxic gas molecules [23]. The metal doped on surfaces of nanostructures are catalytic positions and possible sites for adsorption of toxic gas molecules [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors provide limited mass transfer in the liquid-phase reaction inside a BCR. Hence, it is necessary to identify the various superficial ozone gas velocities and evaluate their effect on the reactor's performance [47][48][49][50][51][52][53][54]. Therefore, the main objective of the present work is to enhance the ozonation reaction to attain a high phenol removal from the wastewater when using an ozonized packed BCR, as well as to evaluate the influence of the hydrodynamic behavior and packing material on the reactor's performance.…”
Section: Introductionmentioning
confidence: 99%